MANUSIA DI TENGAH PANDEMI COVID-19 DALAM PERSPEKTIF DAOISME Refleksi Filosofis Prinsip Wu Wei atas Krisis Kemanusiaan di Tengah Pandemi Covid-19 - Anjelinus Loi (Aggiornamento, 2021)
The focus of this paper is to offer as well as explore Wu Wei's wisdom principles as a way of life to find human harmony in himself and others amid the Covid-19 pandemic. The current disaster, especially the Covid-19 virus, which has a bad impact makes humans worry about its existence. Therefore, humans need a